Heat shock protein 90 inhibition attenuates inflammation in models of atopic dermatitis: a novel mechanism of action - Ben Abdallah, Hakim; Bregnhøj, Anne; Ghatnekar, Gautam; Iversen, Lars; Johansen, Claus (Frontiers in Immunology, 2024)
Background: Heat shock protein 90 (HSP90) is an important chaperone supporting the function of many proinflammatory client proteins. Recent studies indicate HSP90 inhibition may be a novel mechanism of action for inflammatory skin diseases; however, this has not been explored in atopic dermatitis (AD). Objectives: Our study aimed to investigate HSP90 as a novel target to treat AD. Methods: Experimental models of AD were used including primary human keratinocytes stimulated with cytokines (TNF/IFNγ or TNF/IL-4) and a mouse model established by MC903 applications. Results: In primary human keratinocytes using RT-qPCR, the HSP90 inhibitor RGRN-305 strongly suppressed the gene expression of Th1-(TNF, IL1B, IL6) and Th2-associated (CCL17, CCL22, TSLP) cytokines and chemokines related to AD. We next demonstrated that topical and oral RGRN-305 robustly suppressed MC903-induced AD-like inflammation in mice by reducing clinical signs of dermatitis (oedema and erythema) and immune cell infiltration into the skin (T cells, neutrophils, mast cells). Interestingly, topical RGRN-305 exhibited similar or slightly inferior efficacy but less weight loss compared with topical dexamethasone. Furthermore, RNA sequencing of skin biopsies revealed that RGRN-305 attenuated MC903induced transcriptome alterations, suppressing genes implicated in inflammation including AD-associated cytokines (Il1b, Il4, Il6, Il13), which was confirmed by RT-qPCR. Lastly, we discovered using Western blot that RGRN-305 disrupted JAK-STAT signaling by suppressing the activity of STAT3 and STAT6 in primary human keratinocytes, which was consistent with enrichment analyses from the mouse model. Conclusion: HSP90 inhibition by RGRN-305 robustly suppressed inflammation in experimental models mimicking AD, proving that HSP90 inhibition may be a novel mechanism of action in treating AD.